2003
DOI: 10.1046/j.1365-2141.2003.04299.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up of patients with progressive multiple myeloma undergoing allografts after reduced‐intensity conditioning

Abstract: Summary. Allogeneic stem cell transplantation (allo‐SCT) after reduced‐intensity conditioning was evaluated in 22 patients (median age 53, range 36–66 years) with multiple myeloma with progression after an autologous SCT. Seven patients received a transplant from a human leucocyte antigen (HLA)‐identical sibling and 15 patients (68%) from an unrelated donor [including 3/22 (14%) from a HLA‐mismatched unrelated donor]. Graft‐versus‐host disease (GVHD) prophylaxis consisted of serotherapy with antithymocyte glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 29 publications
(24 reference statements)
8
59
0
3
Order By: Relevance
“…Even if the true value of lenalidomide post allograft can only be determined by a prospective randomised study, the relative long PFS of 52% at 3 years is higher than the reported 3-year PFS in similar allogeneic studies without lenalidomide. 2,3,8,9 In the current trial, neither del 13q14 or the use of mismatch donors could be identified as risk factor for survival. As data about t(4;14) or 17p were not available in all patients, a detailed cytogenetic impact could not be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the true value of lenalidomide post allograft can only be determined by a prospective randomised study, the relative long PFS of 52% at 3 years is higher than the reported 3-year PFS in similar allogeneic studies without lenalidomide. 2,3,8,9 In the current trial, neither del 13q14 or the use of mismatch donors could be identified as risk factor for survival. As data about t(4;14) or 17p were not available in all patients, a detailed cytogenetic impact could not be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In comparison to standard myeloablative conditioning regimen, reduced-intensity conditioning regimen resulted in lower non-relapse mortality (NRM) but also in a higher risk of relapse. 9 Retrospective studies suggest that the intensity of the conditioning regimen correlates with the risk of relapse.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 As of June 2002, 105 MM patients who received a RIC allo-SCT have been reported, 45 with further evidence in other publications that the use of RIC allo-SCT for MM is rapidly growing. 30,[46][47][48] However, issues related to TRM rate, GVHD incidence, and proof of a GVM effect are still unresolved because of considerable heterogeneity in patient selection criteria, conditioning regimens, timing of RIC allo-SCT (after autologous transplantation, in complete or partial remission, or after relapse), and comorbid conditions (age and exclusion criteria due to other organ dysfunction). In the series of RIC allo-SCT for MM reported by Badros et al, 28 TRM in the first 100 days was 10% comparing favorably with results obtained in the myeloablative setting from the same institution.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Two German studies and a study from the MD Anderson center confirmed 2-year survivals of 26-50% for patients who had failed one or more autologous transplants. A study combining data from several centers, including approximately 120 patients, found that relapse from a prior autologous transplant was the most significant risk factor for transplant mortality (HR 2.80; P = 0.02), relapse (HR 4.14; P < 0.001), and death (HR 2.69; P = 0.005).…”
Section: Non-ablative Allogeneic Transplantsmentioning
confidence: 99%
“…[21] Several other studies of reduced-intensity allografts from family members or unrelated donors have confirmed that results are poor when patients have failed a prior autologous transplant or have chemotherapy-resistant disease. [22][23][24] Two German studies and a study from the MD Anderson center confirmed 2-year survivals of 26-50% for patients who had failed one or more autologous transplants. A study combining data from several centers, including approximately 120 patients, found that relapse from a prior autologous transplant was the most significant risk factor for transplant mortality (HR 2.80; P = 0.02), relapse (HR 4.14; P < 0.001), and death (HR 2.69; P = 0.005).…”
Section: Non-ablative Allogeneic Transplantsmentioning
confidence: 99%